2004
DOI: 10.1002/cncr.20738
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of intraoperative imprint cytology for sentinel lymph node evaluation in the treatment of breast carcinoma

Abstract: BACKGROUND.The current report provides results from a large retrospective analysis of intraoperative imprint cytology performed on axillary sentinel lymph nodes (IIC N ) removed over the course of 2137 breast surgeries (4905 lymph nodes). It is hoped that these results may serve as benchmarks for those interested in using this technique. METHODS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(34 citation statements)
references
References 59 publications
2
29
0
3
Order By: Relevance
“…Different studies have compared these techniques with regard to the following three considerations -speed (required time-to-report), reliability and cost-effectiveness. 12,13 In our study, time-to-report TIC fitted comfortably with average times for completion of breast surgery. Although the average time taken for reporting TIC appears acceptable, the additional anaesthetic time in a minority of patients must be offset against the increased operating time involved in a delayed axillary clearance.…”
Section: Discussionmentioning
confidence: 54%
“…Different studies have compared these techniques with regard to the following three considerations -speed (required time-to-report), reliability and cost-effectiveness. 12,13 In our study, time-to-report TIC fitted comfortably with average times for completion of breast surgery. Although the average time taken for reporting TIC appears acceptable, the additional anaesthetic time in a minority of patients must be offset against the increased operating time involved in a delayed axillary clearance.…”
Section: Discussionmentioning
confidence: 54%
“…In the study by Creager, the use of imprint cytology did not show any difference in sensitivity, specificity or accuracy between ILC and IDC, whereas the sensitivity for detecting macrometastases in patients with ILC was higher than for detecting micrometastases [47]. Conversely, in the series by Cox et al, the same method was associated with lower sensitivity rates for ILC compared with IDC [48].…”
Section: Hormone-replacement Therapy and Lobular Cancersmentioning
confidence: 62%
“…However, its limitations include relatively high false-negative results (range 0.9-9.0%) and underestimation of disease with a wide range (17), suggesting that it is necessary to perform intraoperative assessment for patients with DCIS diagnosed by core needle biopsy who may need SLNB. Studies have indicated that lobular histology may be more difficult to interpret using touch imprint cytology, leading to a higher false-negative rate (18). Lobular carcinomas were excluded in our study due to the limited number of cases (4 cases), and we focused on the ductal carcinoma type.…”
Section: Discussionmentioning
confidence: 99%